Application of Novel Quantitative Proteomic Technologies to Identify New Serological Biomarkers in Autoimmune Diseases - Lee, Soyoung; Serada, Satoshi; Fujimoto, Minoru; Naka, Tetsuji (IntechOpen, 2011)
None